2021
DOI: 10.3389/fnut.2021.630586
|View full text |Cite
|
Sign up to set email alerts
|

Increased Screen Time Is Associated With Alcohol Desire and Sweetened Foods Consumption During the COVID-19 Pandemic

Abstract: Background: Elevated screen time has been associated with addictive behaviors, such as alcohol and sugar intake and smoking. Considering the substantial increase in screen time caused by social isolation policies, this study aimed to analyze the association of increased screen time in different devices during the COVID-19 pandemic with consumption and increased desire of alcohol, smoking, and sweetened foods in adults.Methods: A sample of 1,897 adults with a mean age of 37.9 (13.3) years was assessed by an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
1
31
2
2
Order By: Relevance
“…Concerning quality assessment, 26 studies out of 95 ( 20 , 27 , 30 , 38 , 40 , 43 , 51 , 61 , 62 , 71–73 , 75 , 83 , 84 , 90 , 91 , 95 , 97 , 98 , 100 , 102 , 104 , 106 , 112 , 113 ) were considered of low quality (27.4%), having a JBI score <70% ( Supplemental Tables 4 and 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning quality assessment, 26 studies out of 95 ( 20 , 27 , 30 , 38 , 40 , 43 , 51 , 61 , 62 , 71–73 , 75 , 83 , 84 , 90 , 91 , 95 , 97 , 98 , 100 , 102 , 104 , 106 , 112 , 113 ) were considered of low quality (27.4%), having a JBI score <70% ( Supplemental Tables 4 and 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Quarantining can also contribute to other obesogenic behaviors, such as increased desire to consume sweets and alcohol (Tebar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of the Internet era, however, the usage of mobile phones has surpassed that of viewing television [ 19 ]. Few studies have suggested that the increase in mobile phone usage is linked to increased intake of SSF [ 20 ]. Yet, the amount of time spent using mobile phones alone does not fully reflect the physical, psychological, and behavioral characteristics of mobile phone users.…”
Section: Introductionmentioning
confidence: 99%